1989
DOI: 10.2527/jas1989.6781972x
|View full text |Cite
|
Sign up to set email alerts
|

Production Characters of Straightbred, F and F Cows:Birth and Weaning Characters of Terminal-Cross Calves

Abstract: Records of 2,449 births and 2,120 weanings of terminal-cross calves were used to characterize maternal productivity of first- and second-generation cows from a diallel of Angus, Brahman, Hereford, Holstein and Jersey when mated to third-breed sires. Third- and later-parity cows were randomly assigned after each parturition to Charolais and Red Poll bulls in multiple-sire pastures. Calves were weaned at approximately 7 mo of age; males were not castrated. A mixed model was assumed for data analysis. Effects inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Therefore, crossbred cows in this study did not provide a stronger in utero environment effect to increase the probability of dystocia as it is affected by calf birth weight. Studies of McDonald & Turner (1972), Dillard et al (1980), Sacco et al (1989), Van Zyl (1990 and Arthur et al (1994Arthur et al ( ,1999 are in general agreement with the existence of nonsignificant maternal heterotic effects for BW. In most investigations (Cundiff et al, 1974;Roberson et al, 1986;Dearborn et al, 1987;Elzo et al, 1990;Schoeman et al, 1993) significant maternal heterotic effects for BW have been reported.…”
Section: Resultssupporting
confidence: 58%
“…Therefore, crossbred cows in this study did not provide a stronger in utero environment effect to increase the probability of dystocia as it is affected by calf birth weight. Studies of McDonald & Turner (1972), Dillard et al (1980), Sacco et al (1989), Van Zyl (1990 and Arthur et al (1994Arthur et al ( ,1999 are in general agreement with the existence of nonsignificant maternal heterotic effects for BW. In most investigations (Cundiff et al, 1974;Roberson et al, 1986;Dearborn et al, 1987;Elzo et al, 1990;Schoeman et al, 1993) significant maternal heterotic effects for BW have been reported.…”
Section: Resultssupporting
confidence: 58%